Immunoglobulin and other proteins in the cerebrospinal fluid of patients with Alzheimer's disease. - Chapel, H; Esiri, M; Wilcock, G (1984)
Immunoglobulin has been measured and studied electrophoretically in cerebrospinal fluid (CSF) from 14 patients with Alzheimer's disease and 25 undemented controls. Presence or absence of the diagnosis of Alzheimer's disease was confirmed histologically, as these were postmortem specimens. There was no increased incidence of oligoclonal IgG bands in either group, and no significant differences in the levels of IgG and albumin. Non-immunoglobulin bands were found in the gamma region in some samples from Alzheimer's disease patients and controls; such bands are not found in the CSF from younger patients. There was a significantly increased incidence of double transferrin and double tau protein bands in the Alzheimer's group, suggesting that further studies of genetic markers might be worthwhile.